Profit optimization for bulk carrier discharging at tidal port : an operational perspective - Li, Lei (2017)
If a vessel is going to discharge cargo at a tidal port, the draft at the time of arrival is very much concerned by different parties including ship owner and operator, and cargo owner because the draft is closely related to how much cargo can be loaded onto the vessel and thus freight chargeable. However, decision-making in this situation is not clear-cut since particulars of the designated vessel, decisions on sailing speed, current market freight and hire rate, bunker price, etc will all affect the profitability of a trade. Existing operational decision-making approach usually planning manually by simple optimizing calculation without considering the tradeoffs among decision variables. However, conservative or incomprehensive planning is compromising the utilization of vessels and reducing the profitability of a voyage. Hence, development of optimization based decision-support model is crucial for an efficient operational decision concerning vessels discharging at tidal ports. This proposal constructs a model to assist shipping operators in determining optimal proceeding speed and cargo quantity in accordance with the time-dependent draft at discharging port while synthetically consider particulars of the employed vessel and current market condition. The paper provides an analytical solution to the real world problem and offers an intuition into how variables and their interactions affect the result.